Efektivitas Multimedia Interaktif dan Mobile Learning dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Seni Budaya - Irwanto Irwanto Irwanto; Riki Ahmad Taufik; Hudiana Hernawan; Syamsul Rizal (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2019)
Abstract : Learning outcomes in Cultural Arts subjects to date have not yet reached the competency standards set by the KKM. One of the factors causing low learning outcomes is the cognitive low level of students' understanding of dance theory. This shows that the learning process of cultural arts needs to be developed with a different learning approach. The problem in this study is whether there are: (1) improvement in learning outcomes of class XI students who use Interactive Multimedia? (2) increase learning outcomes of class XI students who use Mobile Learning? and (3) differences in the increase in learning outcomes of class XI students who use Interactive Multimedia with Mobile Learning on the subject matter of Dance Art in Garut 8? The research method used was quasi-experimental with the design of the Static Group Prestest-Posttest Design. The results of the study show: 1) there is an increase in learning outcomes of class XI students who use Interactive Multimedia with an increase in student learning outcomes obtained included in the high category; 2) there is an increase in learning outcomes of class XI students who use Mobile Learning with an increase in student learning outcomes obtained included in the high category; and 3) there are differences in the increase in learning outcomes of class XI students who use Interative Multimedia with Mobile Learning. The use of Interactive Multimedia is more effective in improving learning outcomes compared to mobile learning in the subject matter of dance material in Cultural Arts subjects at SMK 8 8 Garut. Abstrak : Hasil belajar pada mata pelajaran Seni Budaya sampai saat ini belum mencapai standar kompetensi yang telah ditentukan KKM. Salah satu faktor penyebab rendahnya hasil belajar adalah masih rendahnya pemahaman siswa secara kognitif terhadap teori seni tari. Hal tersebut menunjukan proses pembelajaran seni budaya ini perlu dikembangkan dengan pendekatan pembelajaran yang berbeda. Permasalahan pada penelitian ini apakah terdapat: (1) peningkatan hasil belajar siswa kelas XI yang menggunakan Multimedia Interaktif? (2) peningkatan hasil belajar siswa kelas XI yang menggunakan Mobile Learning? dan (3) perbedaan peningkatan hasil belajar siswa kelas XI yang menggunakan Multimedia Interaktif dengan Mobile Learning pada pokok bahasan materi Seni Tari di SMKN 8 Garut? Metode Penelitian yang digunakan adalah kuasi eksperimen dengan desain the Static Group Prestest-Posttest Design. Hasil penelitian menunjukan: 1) terdapat peningkatan hasil belajar siswa kelas XI yang menggunakan Multimedia Interaktif dengan peningkatan hasil belajar siswa yang diperoleh termasuk dalam kategori tinggi; 2) terdapat peningkatan hasil belajar siswa kelas XI yang menggunakan Mobile Learning dengan peningkatan hasil belajar siswa yang diperoleh termasuk dalam kategori tinggi; dan 3) terdapat perbedaan peningkatan hasil belajar siswa kelas XI yang menggunakan Multimedia Interatif dengan Mobile Learning. Penggunaan Multimedia Interaktif lebih efektif dalam meningkatkan hasil belajar dibandingkan dengan mobile learning pada pokok bahasan materi seni tari pada mata pelajaran Seni Budaya di SMKN 8 Garut.